PHYSIOLOGICAL AND BIOCHEMICAL PROPERTIES ANALYSIS OF LATE-BOLTING TRANSGENIC CHINESE CABBAGE (B RASSICA RAPA L. SSP. PEKINENSIS) - G. Q. Xia; Q. W. He; S. Y. Zhao (Journal of Animal and Plant Sciences, 2015)
LFYgene plays important roles in determining plant flowering mainly by controlling the timing of phase transition. Constitutive under-expression of LFY gene in Arabidopsis resulted in the formation of late flowering and highly branching phenotype. In this paper, we investigated some physiological and biochemical properties of the transformantsthat were down-regulated LFY gene expression to delay bolting and flowering of Chinese cabbage (Brassica rapa L. ssp. pekinensis) by RNAi approach. The results showed that transgenic plants had more leaves, but a shorter height compared to control. Meanwhile, it was greatly reduced whatever the expression of LFY gene and the content of soluble sugar, sucrose, starch, IAA, GA, ABA, or activities of peroxidase, α-amylase and esterase, although soluble protein content and zeatin were increased. All results indicated that the variation of nutrient metabolism and endogenous hormones were the root of late-bolting and flowering in transformants. They affected different signal transduction pathways and induced late-bolting and flowering
Keywords: Chinese cabbage; LFY gene; RNA interference; physiological biochemistry properties